Dietary Patterns Characterized by High Meat Consumption Are Associated with Other Unhealthy Life Styles and Depression Symptoms - Gregório, Maria João; Rodrigues, Ana M.; Eusébio, Mónica; Sousa, Rute Dinis; Dias, Sara; André, Beate; Grønning, Kjersti; Coelho, Pedro S.; Mendes, Jorge M.; Graça, Pedro; Espnes, Geir A.; Branco, Jaime C.; et al. (Frontiers in Nutrition, 2017)
Objective: We aimed to identify dietary patterns (DP) of Portuguese adults, to assess their socioeconomic, demographic, lifestyle determinants and to identify their impact on health. Design: EpiDoC 2 study included 10,153 Portuguese adults from the EpiDoC Cohort, a population based study. In this study, trained research assistants using computed assisted telephone interview collected socioeconomic, demographic, dietary, lifestyles and health information from March 2013 to July 2015. Cluster analysis was performed, based on questions regarding the number of meals, weekly frequency of soup consumption, vegetables, fruit, meat, fish, dairy products and daily water intake. Factors associated with DP were identified through logistic regression models. Results: Two DPs were identified: the “meat dietary pattern” and the “fruit & vegetables dietary pattern”. After multivariable adjustment, women (OR=0.52; p0.001), older adults (OR=0.97; p0.001) and individuals with more years of education (OR=0.96; p=0.025) were less likely to adopt the “meat dietary pattern”, while individuals in a situation of job insecurity/unemployment (OR=1.49; p=0.013), Azores islands residents (OR=1.40; p=0.026), current smoking (OR=1.58; p=0.001), daily alcohol intake (OR=1.46; p=0.023) and physically inactive (OR=1.86; p0.001) were positively and significantly associated with “meat dietary pattern”. Moreover, individuals with depression symptoms (OR=1.50; p=0.018) and the ones who did lower number of medical appointments in the previous year (OR=0.98; p=0.025) were less likely to report this DP. Conclusions: Our results suggest that unhealthy DPs (meat dietary pattern) are part of a lifestyle behaviour that includes physical inactivity, smoking habits and alcohol consumption. Moreover, depression symptoms are also associated with unhealthy DPs.